Penerapan Hukum Indonesia Terhadap Tindak Pidana Pornografi bagi Pelaku dengan Eksibisionisme - Putri Aisyah Cahyani; Hery Firmansyah (UNES Law Review, 2023)
The pornography case was committed by Siskae who created pornographic content on the social media onlyfans, where Siskae's actions constituted a criminal act of pornography, where Siskae suffered from the mental disorder of exhibitionism, namely sexual deviation that occurs to a person which causes the sufferer to experience increased sexual arousal when he shows a tool. her gender. Due to Siskae's mental disorder, Siskae, based on Article 44 of the Criminal Code regarding justification and forgiveness, received a reduced sentence and restorative justice could be implemented.